RESENHA: Cumulative Environmental Assessment - Diniz, Noris Costa (Revista do Departamento de Geografia, 2011)
SHOEMAKER, D. J. Cumulative environmental assessment. Department of Geography Publication Series Number 42. University of Waterloo. Waterloo, CA. 1994. 129 p.